(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
Differences between spatial and functional positions of lichen and bryophyte associations vs. higher plant communities are shown. We recognized four lichen associations in the lower Dnieper sand dunes: Сladonietum alcicornis Klement (1953), Xanthoparmelietum pokornyi Khodosovtsev ass. nova, Placynthiello uliginosi-Cladonietum rei Khodosovtsev ass. nova, Cladonietum subulato-fimbriatae Khodosovtsev ass. nova; all belonging to the union Cladonion sylvaticae Klement (1950) from the order Peltigeretalia Klement (1950). One bryophyte association, Syntrichietum ruraliformis Boiko et Khodosovtsev ass. nova, was recognized; it belongs to the union Ceratodonto-Polytrichion piliferi (Waldh. 1947) v. Hübschm. (1967) from the order Polytrichetalia piliferi v. Hübschm. (1975). We consider the stage of stabilization of the substrate as the leading factor in succession of terricolous lichen and moss communities on sand dunes at lower Dnieper. With increasing of stabilization of weathering, lichen and bryophyte communities alternate in the following order: (1) Placynthiello uliginosi-Cladonietum rei; (2) Cladonietum subulato-fimbriatae; (3) Xanthoparmelietum pokornyi; (4) Cladonietum alcicornis. Placуnthiella uliginosa growing on sand dunes forms pyramid-forming or pancake-forming microrelief, which indicate intensities of weathering vs. stabilization.